1996
DOI: 10.1084/jem.184.3.1093
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic expression of interleukin-4 abrogates insulitis and autoimmune diabetes in nonobese diabetic (NOD) mice.

Abstract: SummaryDiabetes in nonobese diabetic (NOD) mice is a T cell-dependent autoimmune disease. The destructive activities of autoreactive T cells have been shown to be tightly regulated by effector molecules. In particular, T helper (Th) 1 cytokines have been linked to diabetes pathogenesis, whereas Th2 cytokines and the cells that release them have been postulated to be protective from disease. To test this hypothesis, we generated transgenic NOD mice that express interleukin (IL) 4 in their pancreatic [3 cells un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
143
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(152 citation statements)
references
References 45 publications
7
143
2
Order By: Relevance
“…Interestingly, we previously have reported that the expression of GM-CSF in pancreatic gcells does not trigger diabetes in BALB/c mice [41], suggesting that genetic predisposition determines the specific peptide antigens to be presented precipitating clinical diabetes. In addition, preliminary observations showed that in a functionally tolerant model (NOD-IL-4) [42], pancreatic expression of GM-CSF can lead to the appearance of clinical disease in both, females and males, suggesting that affecting antigen presentation can precipitate disease in a non-pathogenic environment. Together, our data are consistent with recent findings showing that DC vaccination consistently triggers clinical autoimmunity in genetically susceptible subjects [22].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we previously have reported that the expression of GM-CSF in pancreatic gcells does not trigger diabetes in BALB/c mice [41], suggesting that genetic predisposition determines the specific peptide antigens to be presented precipitating clinical diabetes. In addition, preliminary observations showed that in a functionally tolerant model (NOD-IL-4) [42], pancreatic expression of GM-CSF can lead to the appearance of clinical disease in both, females and males, suggesting that affecting antigen presentation can precipitate disease in a non-pathogenic environment. Together, our data are consistent with recent findings showing that DC vaccination consistently triggers clinical autoimmunity in genetically susceptible subjects [22].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this view, efficient induction of regulatory Th2 cells in NOD mice has been achieved by systemic treatment with IL-4 or its local expression in pancreatic g -cells in insulin-promoter-IL-4 transgenic mice [14,15]. Based on the Th1/Th2 paradigm, it has been postulated that IL-4 induces a shift in the balance of anti-islet T cells from the pathogenic Th1 toward a less harmful Th2 phenotype.…”
Section: Introductionmentioning
confidence: 90%
“…When transgenically expressed in the pancreatic ␤-cells of nonobese diabetic mice or in the CNS of SJL/J mice, IL-4 prevented autoimmune diabetes and experimental allergic encephalomyelitis development, respectively (30,31). APC alternatively activated by IL-4 might thus play a role in controlling the response of T lymphocytes to Ags presented by peripheral tissues.…”
Section: Discussionmentioning
confidence: 99%